Blasto-ing through the chest wall: Empyema necessitans due to pulmonary blastomycosis - Cameron G. Gmehlin; Nicholas P. Bergeron; Vaishnavi Ramesh; Haris Akhtar; Zelalem Temesgen (IDCases)
Empyema necessitans is a rare complication of empyema and often associated with chronic, untreated infections. Here we report a case of a 28-year-old male who presented with cough, fever, pleuritic chest pain, and left chest wall mass who was found to have empyema necessitans caused by Blastomycosis dermatiditis. He was neither immunocompromised nor had exposures to soil or freshwater sources. Empyema necessitans caused by Blastomyces is rare, with only three other case reports published in the literature. We write to raise awareness of this phenomenon and highlight the importance of maintaining strong clinical suspicion for fungal etiologies of chronic constitutional and pulmonary symptoms, especially when unresponsive to empiric antibiotics.